School as community : from promise to practice - Furman, Gail C., 1946- (State University of New York Press, 2002)
Annotation. Seventeen scholars from the U.S. and Canada contribute 12 chapters exploring the promise of school community, the issues associated with it, and some implications for administration and leadership. The text focuses on K-12 and developing a sense of community within the school, emphasizing in particular the challenges in schools with highly diverse populations, and including coverage of the dynamic relationship between schools and their adjacent communities. Annotation copyrighted by Book News, Inc., Portland, OR
Keywords: School management and organization -- United States.; Community and school -- United States.; Administration scolaire -- États-Unis.; EDUCATION -- Teaching Methods & Materials -- General.; Community and school; School management and organization; United States